2021
DOI: 10.1111/ctr.14319
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of pre‐operative pregabalin reduces post‐operative opioid use after orthotopic liver transplantation

Abstract: The opioid epidemic remains a critical public health crisis with an estimated 46 802 overdose deaths in the United States in 2018, accounting for 69.5% of all drug overdose deaths. 1 Furthermore, the economic impact of prescription opioid-related overdose, abuse, and dependence is estimated to exceed 78.5 billion dollars annually. 2 A rising clinical dilemma facing healthcare providers in the midst of the opioid crisis has been the appropriate use of opioids for post-surgical pain management. Despite the known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Within this population, there were various assessments of nonopioid analgesic medications in the postoperative transplant setting. Eleven studies evaluated the impact of a single opioid‐sparing medication including pregabalin, continuous systemic lidocaine, and local anesthetics (single and continuous dosing) 18,37–46 . Furthermore, seven studies evaluated the impact of a multimodal analgesic strategies, and two assessed the impact of different education‐based interventions 19–21,47–52 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within this population, there were various assessments of nonopioid analgesic medications in the postoperative transplant setting. Eleven studies evaluated the impact of a single opioid‐sparing medication including pregabalin, continuous systemic lidocaine, and local anesthetics (single and continuous dosing) 18,37–46 . Furthermore, seven studies evaluated the impact of a multimodal analgesic strategies, and two assessed the impact of different education‐based interventions 19–21,47–52 …”
Section: Resultsmentioning
confidence: 99%
“…Efficacy outcomes were variable, but generally included evaluation of opioid use and PRPS. Each comparative study demonstrated a statistically significant reduction in opioid use for those who received the various minimization intervention(s) 18–21,37–42,47–52 . Patient‐reported pain scales were also evaluated, but the impact of opioid minimization interventions varied by study 19,37,41,42,50 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations